2023
DOI: 10.3389/fmed.2023.1128981
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and patterns of severe Plasmodium vivax monoinfection in Vietnam: a 4-year single-center retrospective study

Abstract: IntroductionInfection with Plasmodium vivax is a recognized cause of severe malaria including deaths. The exact burden and patterns of severe P. vivax monoinfections is however still not well quantified, especially in P. vivax endemic regions. We examined the magnitude and patterns of severe malaria caused by monoinfections of P. vivax and associated predictors among patients admitted to a tertiary care center for malaria in Vietnam.MethodsA retrospective cohort study was conducted based on the patients’ medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The flow of malaria patients clearly revealed that they were inclined to choose primary health institutions closer to their homes for the first visit. Combined with many previous studies, the reasons can be explained as that most of the imported malaria patients are overseas workers, who are less aware of malaria prevention and treatment [ 28 , 37 39 ]. Moreover, the medical treatment decisions are constrained by economic conditions, so primary health institutions with low prices are the preferred choice of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The flow of malaria patients clearly revealed that they were inclined to choose primary health institutions closer to their homes for the first visit. Combined with many previous studies, the reasons can be explained as that most of the imported malaria patients are overseas workers, who are less aware of malaria prevention and treatment [ 28 , 37 39 ]. Moreover, the medical treatment decisions are constrained by economic conditions, so primary health institutions with low prices are the preferred choice of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ow of malaria patients clearly revealed that they were inclined to choose primary health institutions closer to their homes for the rst visit. Combined with many previous studies, the reasons can be explained as that most of the imported malaria patients are overseas workers, who are less aware of malaria prevention and treatment [29,[38][39][40]. Moreover, the medical treatment decisions are constrained by economic conditions, so primary health institutions with low prices are the preferred choice of patients.…”
Section: Discussionmentioning
confidence: 99%